DIFFUSION IN IRON AND ITS ALLOYS AFTER SATURATION OF THE SURFACE WITH ARGON AND KRYPTON IONS DURING ANNEALING AND PULSED LOADING - Mazanko, V. F.; Gertsriken, D. S.; Novomlynets, О. A.; Mironov, D. V.; Mironov, V. M. (Cherkasy University Bulletin: Physical and Mathematical Sciences, 2019)
The effect of the preliminary introduction of inert gases (argon and krypton) into iron and its alloys in a glow discharge plasma on diffusion (mass transfer) under various external influences was studied using methods based on the use of radioactive isotopes and xrays. The studies were carried out by methods of x-ray diffraction analysis, layered radiometric analysis of residual integral activity, macro-, micro-, electron-microscopic and activation autoradiography. Isotopes of iron 55Fe, nickel 63Ni, carbon 14C, argon 41Ar and krypton 85Kr were used. The following external effects were applied to the metal (alloy) in the initial state and after saturation with an inert gas: galvanic coating, isothermal annealing, athermal martensitic transformation with explosive kinetics and a large volume effect (~ 3%), ultrasonic impact treatment, compression due to deformation when the load falls, magnetic pulse deformation, etc. It is shown that the presence of a pre-introduced inert in iron and alloys based on it leads to a decrease in the mobility of atoms during annealing, low-temperature pulsed loading in a wide range of deformation rates, and further ion bombardment in a glow discharge. No difference was found in the effect of the type of inert gas — argon or krypton — on the change in atomic mobility, surface distribution, and the shape of the concentration profile. The barrier effect of the introduced gas is associated with structural-phase changes in the surface layers by the occurrence of gas-filled pores and a subtraction solid solution in the surface layers, which transforms into a substitutional solid solution away from the surface. Additional studies have shown that the barrier effect of the introduced inert gas on diffusion during subsequent exposures is observed not only on iron, but also on copper and aluminum. This effect is especially pronounced during the subsequent ion bombardment of copper and aluminum saturated with one or another inert gas in a krypton or argon medium as compared to the subsequent pulsed compression or deformation under martensitic transformations. This suggests the universal nature of the discovered regularity. It should be noted according to autoradiographic studies that the presence of an inert gas, which slows down the transfer of matter during subsequent treatments, does not change the nature of the distribution of atoms. There is diffusion over the grain volume with some depletion of the surface layer, and the concentration profiles are described by an exponential dependence on the square of the penetration depth. Therefore, the mechanism of volume diffusion is preserved over the entire range of temperatures and strain rates, and also does not depend on the type of external influence applied. This is true for native atoms and atoms forming solid solutions of various types: substitution (nickel), interstitial (carbon), subtraction (argon and krypton).